2005
DOI: 10.1007/s00425-005-0116-9
|View full text |Cite
|
Sign up to set email alerts
|

Sodium nitroprusside, cyanide, nitrite, and nitrate break Arabidopsis seed dormancy in a nitric oxide-dependent manner

Abstract: The seeds of many plant species are dormant at maturity and dormancy loss is a prerequisite for germination. Numerous environmental and chemical treatments are known to lessen or remove seed dormancy, but the biochemical changes that occur during this change of state are poorly understood. Several lines of research have implicated nitric oxide (NO) as a participant in this process. Here, we show that dormant seeds of Arabidopsis thaliana (L.) Heynh. will germinate following treatment with the NO donor sodium n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
173
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(180 citation statements)
references
References 24 publications
3
173
1
3
Order By: Relevance
“…The mode of action of cyanide in stimulating seed germination remains unclear but is thought to involve reactive oxygen species 32,39 . It has also been proposed that cyanide acts at an initial step in dormancy alleviation and nitrogen oxide is required at a later step 33 . This is interesting given that nitrogen oxides (NO and NO 2 ) have previously been proposed as germination-active components of smoke and can stimulate the germination of E. penduliflora 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mode of action of cyanide in stimulating seed germination remains unclear but is thought to involve reactive oxygen species 32,39 . It has also been proposed that cyanide acts at an initial step in dormancy alleviation and nitrogen oxide is required at a later step 33 . This is interesting given that nitrogen oxides (NO and NO 2 ) have previously been proposed as germination-active components of smoke and can stimulate the germination of E. penduliflora 8 .…”
Section: Discussionmentioning
confidence: 99%
“…3 h) at relatively high concentration (ca. 1 mM) followed by removal of the cyanide source 32,33 . We tested KCN at various concentrations in a continuous incubation mode and found that it promoted the germination of A. manglesii at concentrations similar to those found effective for glyceronitrile (Fig.…”
Section: Confirmation Of Germination Activitymentioning
confidence: 99%
“…Sodium nitroprusside (SNP), producing both NO and HCN in the light (Feelisch 1998), releases dormancy of lettuce (Beligni and Lamattina 2000), barley (Bethke et al 2004), Arabidopsis (Bethke et al 2004(Bethke et al , 2006a, A. retroflexus seeds (Liu et al 2011) and Malus domestica embryos (Gniazdowska et al 2007(Gniazdowska et al , 2010. Likewise, HCN released from Fe(II)CN or Fe(III)CN can reduce dormancy in Arabidopsis (Bethke et al 2006b), A. retroflexus seeds (Liu et al 2011) and Malus domestica embryos (Gniazdowska et al 2010). There are no data on the effect of gibberellins, ethylene, NO and HCN on germination of dry stored or stratified A. retroflexus seeds.…”
Section: Introductionmentioning
confidence: 99%
“…However, NO exerts both beneficial and harmful effects on plants, depending on its concentrations in cells [15]. Several papers have reported that NO is an endogenous regulator of seed dormancy, illustrated by the NO donor compounds breaking dormancy of Arabidopsis seeds [16][17][18] and reducing dormancy of three barley cultivars [17]. Conversely, NO scavengers have been shown to strengthen dormancy of Arabidopsis and barley seeds [17,18], and reduce the stimulative effects of NO donors on seed germination [10,17].…”
Section: Introductionmentioning
confidence: 99%
“…Several papers have reported that NO is an endogenous regulator of seed dormancy, illustrated by the NO donor compounds breaking dormancy of Arabidopsis seeds [16][17][18] and reducing dormancy of three barley cultivars [17]. Conversely, NO scavengers have been shown to strengthen dormancy of Arabidopsis and barley seeds [17,18], and reduce the stimulative effects of NO donors on seed germination [10,17]. Beligni and Lamattina [10] concluded that NO was involved in light-mediated signaling, such as light stimulation of seed germination, de-etiolation and inhibition of hypocotyl elongation.…”
Section: Introductionmentioning
confidence: 99%